Evaluation of Wheelchair Fit and Its Impact on Physical Comfort in a Community-Based Program in Malang - Firnanda, Sani Widya; Fajarningtyas, Mia; Yudiansyah, Anggi Gilang; Lestari, Dwi Indriani; Anggraini, Vivid Prety; Nugroho, Muhammad Barlian (Jurnal Kesehatan Islam : Islamic Health Journal, 2025)
Background: Proper wheelchair fit is essential to ensure comfort, postural stability, and to prevent secondary health complications in individuals with disabilities. In community-based programs, mismatches between wheelchair dimensions and users' anthropometric characteristics often go unnoticed, potentially leading to long-term issues. Objective: This study aims to evaluate the alignment between users’ body dimensions and the wheelchairs distributed through a community-based program in Malang, and to examine the potential ergonomic and clinical implications of mismatched fit. Methods: A descriptive quantitative design was employed, involving 20 full-time wheelchair users selected purposively. Anthropometric measurements (seated height, popliteal length, hip width, elbow height) and wheelchair dimensions (seat height, seat depth, seat width, backrest height, armrest height) were directly measured. Normality was tested using the Shapiro–Wilk test, followed by Pearson correlation analysis. Outliers were identified using z-score thresholds. Results: Significant positive correlations were found between seat height and armrest height (r = 0.65, p < 0.01), and between backrest height and seat width (r = 0.58, p < 0.05). No correlation was found involving seat depth. Two participants showed notable mismatches requiring individual adjustments, highlighting risks such as discomfort, postural imbalance, and mobility limitation. Conclusion: Mismatch between wheelchair dimensions and user anthropometry can contribute to preventable discomfort and postural strain. Personalized assessments and ergonomic adjustments are crucial in community wheelchair programs. These findings support the implementation of anthropometric-based distribution strategies and training for service providers.